PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH, AKSESIBILITAS LAPORAN KEUANGAN DAN KOMITMEN PIMPINAN TERHADAP TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH PADA SKPD DI KABUPATEN KEEROM - Siahaan, Gunung Hasian; Fallah, Syaikhul; Bharanti, B. Elitha (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
Presentation and accessibility of financial statement is influenced by accountability and commitment of management in managing SKPDs’ finances, which also affecting the audit opinion that reflect how well finance of a local government has been managed. The purpose of this study is to examine and analyze the influence of financial statement presentation, accessibility of financial statements and management commitment regarding transparency of financial management at SKPDs in Keerom Regency. Population of this research is around 56 with 94 respondents which categorized as Head of SKPDs and the Expenditure Treasurer on each SKPD that all are assembled as the sample of this study. Then, a random sampling method is constructed as a sample method in conduncting this research. The data collection is done by conducting a survey. While, hypothesis analysis in this study is empirically tested by using Multiple Regression Analysis. This paper find that the area of financial statement presentation has a positive and significant impact on the transparency of management of the Regional Financial reports. While, accessibility of local financial statement has not affect to the transparency of financial management in Keerom Regency. The results also indicate that the leadership commitment has a significant and positive effect on the transparency of financial management in Keerom Regency.